Factors associated with oral health-related quality of life of institutionalized elders - Luiz Fabrício Santos de OLIVEIRA; Rayssa Lucena WANDERLEY; Elza Cristina Farias de ARAÚJO; Mariana Marinho Davino de MEDEIROS; Olívia Maria Costa de FIGUEREDO; Mayara Abreu PINHEIRO; Renata Cunha Matheus RODRIGUES GARCIA; Yuri Wanderley CAVALCANTI (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract This study aimed to evaluate the correlation between two Oral Health-Related Quality of Life (OHRQoL) questionnaires (the Oral Health Impact Profile (OHIP-14) and the Geriatric Oral Health Assessment Index (GOHAI)) and to investigate the factors associated with the OHRQoL of institutionalized elderly individuals. A cross-sectional multicenter study was performed with 344 institutionalized elderly individuals residing in two Brazilian cities. Six trained researchers interviewed the elderly individuals. Sociodemographic data were collected from medical records. Dental caries experience and the use of and need for dentures were recorded through oral examination performed by two trained examiners. A Likert scale (1-5 points) was used to assess general health and self-perceived oral health. The number of chewing cycles needed to chew a portion of peanuts was used to assess the swallowing threshold. The OHIP-14 and GOHAI were used to evaluate OHRQoL, and statistically significant correlations were assessed using Spearman's correlation test (p < 0.05). Poisson regression (p < 0.05) was used to investigate the association of OHRQoL with independent variables. Scores on the OHIP-14 (7.57 ± 8.63) and GOHAI (32.46 ± 3.85) were strongly and inversely correlated (r2 = -0.671, p < 0.001), although these measures were associated with different factors. A higher OHIP-14 total score (worse OHRQoL) was associated with female gender, a greater number of healthy teeth, worse self-perceived general health and oral health, and a lower swallowing threshold (p < 0.05). A higher GOHAI total score (better OHRQoL) was associated with a greater number of filled teeth, better self-perceived oral health and a greater swallowing threshold (p < 0.05). In conclusion, worse OHRQoL among institutionalized elderly individuals is associated with worse self-perceived oral health and a greater swallowing threshold.